Occupational injury among hospital patient‐care workers: What is the association with workplace verbal abuse?. Issue 2 (22nd October 2013) - Sabbath, Erika L.; Hurtado, David A.; Okechukwu, Cassandra A.; Tamers, Sara L.; Nelson, Candace; Kim, Seung‐Sup; Wagner, Gregory; Sorenson, Glorian
Abstract Objective To test the association between workplace abuse exposure and injury risk among hospital workers. We hypothesized that exposed workers would have higher injury rates than unexposed workers. Methods Survey of direct‐care workers (n = 1, 497) in two hospitals. Exposure to workplace abuse was assessed through self‐report; occupational injury reports were extracted from employee records. We tested associations between non‐physical workplace violence and injury using log‐binomial regression and multilevel modeling. Results Adjusted prevalence ratio (PR) for injury associated with being yelled at was 1.52 (95% CI 1.19, 1.95); for experiencing hostile/offensive gestures 1.43 (1.11, 1.82); and for being sworn at 1.41 (1.09, 1.81). In analyses by injury subtypes, musculoskeletal injuries were more strongly associated with abuse than were acute traumatic injuries. Associations operated on group and individual levels and were most consistently associated with abuse perpetrated by patients. Conclusion Exposure to workplace abuse may be a risk factor for injuries among hospital workers. Am. J. Ind. Med. 57:222–232, 2014. © 2013 Wiley Periodicals, Inc.